The association between active tobacco use during pregnancy and growth outcomes of children under five years of age: a systematic review and meta-analysis - Diana Quelhas; Chytanya Kompala; Brittney Wittenbrink; Zhen Han; Megan Parker; Myra Shapiro; Shauna Downs; Klaus Kraemer; Jessica Fanzo; Saul Morris; Katharine Kreis (BMC, 2018)
Abstract Background Despite considerable global efforts to reduce growth faltering in early childhood, rates of stunting remain high in many regions of the world. Current interventions primarily target nutrition-specific risk factors, but these have proven insufficient. The objective of this study was to synthesize the evidence on the relationship between active tobacco use during pregnancy and growth outcomes in children under five years of age. Methods In this systematic review and meta-analysis, six online databases were searched to identify studies published from January 1, 1980, through October 31, 2016, examining the association between active tobacco use during pregnancy and small-for-gestational age (SGA), length/height, and/or head circumference. Ecological studies were not included. A meta-analysis was conducted, and subgroup analyses were carried out to explore the effect of tobacco dosage. Results Among 13,189 studies identified, 210 were eligible for inclusion in the systematic review, and 124 in the meta-analysis. Active tobacco use during pregnancy was associated with significantly higher rates of SGA (pooled adjusted odds ratio [AORs] = 1.95; 95% confidence interval [CI]: 1.76, 2.16), shorter length (pooled weighted mean difference [WMD] = 0.43; 95% CI: 0.41, 0.44), and smaller head circumference (pooled WMD = 0.27; 95% CI: 0.25, 0.29) at birth. In addition, a dose-response effect was evident for all growth outcomes. Conclusion Tobacco use during pregnancy may represent a major preventable cause of impaired child growth and development.